2014
DOI: 10.1364/aop.6.000156
|View full text |Cite
|
Sign up to set email alerts
|

Real photonic waveguides: guiding light through imperfections

Abstract: Real photonic waveguides are affected by structural imperfections due to fabrication tolerances that cause scattering phenomena when the light propagates through. These effects result in extrinsic propagation losses associated with the excitation of radiation and backscattering modes. In this work, we present a comprehensive review on the extrinsic loss mechanisms occurring in optical waveguides, identifying the main origins of scattering loss and pointing out the relationships between the loss and the geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 170 publications
(298 reference statements)
1
51
0
Order By: Relevance
“…These reflections can be caused by an abrupt index variation in the design of the device or due to surface roughness on the waveguides. In [67], it has been shown that LPCVD based SiN waveguides have 5 to 15 dB weaker distributed reflections due to the surface roughness of the waveguides as compared to SOI waveguides. Fig.…”
Section: B Index Contrastmentioning
confidence: 99%
“…These reflections can be caused by an abrupt index variation in the design of the device or due to surface roughness on the waveguides. In [67], it has been shown that LPCVD based SiN waveguides have 5 to 15 dB weaker distributed reflections due to the surface roughness of the waveguides as compared to SOI waveguides. Fig.…”
Section: B Index Contrastmentioning
confidence: 99%
“…1(b)], also called jitter, inherent to any fabrication process, on the performance of SWG waveguide structures. While the effects of fabrication imperfections in conventional channel waveguides and photonic crystal slab waveguides have been extensively studied in the past (see e.g [23]. for a comprehensive review on this topic), the effect of the jitter on the performance of periodic SWG waveguides has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…This situation is common during real circuit fabrications because the exact uncertainties of the fabrication processes are difficult to predict and may change with time. Of course, if the statistics of fabrication variations are precisely known, then we can always solve (9) to get the optimized design under that fabrication variations as done in Section 4.2.…”
Section: Further Discussion On Mses and Yieldmentioning
confidence: 99%
“…On the contrary, stochastic uncertainties related to fabrication variations, such as waveguide geometry deviation, gap opening issues, material composition fluctuations, and surface roughness, are unavoidable in production processes [5][6][7][8][9]. It is well known that such uncertainties can have a dramatic impact on the functionality of fabricated circuits [4,[10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%